Gambaran Pediculosis Pada Anak-Anak Panti Asuhan di Kota Makassar - Arisanti, Dewi; Widyanti, Tuty; Hasnah, Hasnah; Rustiah, Wa Ode; Ernawati, Ernawati (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2024)
Pediculosis is an infectious disease caused by lice with symptoms of itching on various parts of the skin. Living in a crowded environment means that foster children have the same personal hygiene and use shared combs. Orphanage sanitation facilities are not good and the bedrooms are narrow which also affects the cleanliness of every foster child living in the orphanage. This study aims to determine the description of pediculosis in children from orphanages in Jalan Andi Mappaodang, Makassar City. The type of research used in this research is descriptive with laboratory observation tests. The population in this study is all children from the orphanage. The sample used was 20 children in several orphanages. The sampling technique used was purposive sampling with the criteria of age 3-11 years, hair length, and gender. Based on research that has been conducted, all of the 20 lice samples from respondents examined were positive, namely infected with pediculosis, so it can be concluded that children in several orphanages are 100% positive for Pediculosis infection.